Korelasi Genetik Antara Bobot Sapih dengan Bobot Satu Tahun dan Laju Pertumbuhan Pasca Sapih Sapi Brahman Cross - Gushairiyanto, Gushairiyanto; Depison, Depison (Fakultas Peternakan Universitas Jambi, 2009)
Increased production of meat has to be done to meet the needs of the animal protein demand continues to increase, this study aims to look at the possibility of accelerating the implementation of selection with respect to the production of meat that is when the cow weaned in order to improve respos selection. This study collected data includes birth weight, weaning weight, weight of one year and post-weaning growth rate and identify the lineage of every cow that became the object of research. The study was conducted by analyzing the data to obtain heritability value weaning weight, weight of one year and post-weaning growth rate and the value of genetic correlation between cow weight and weight one year post-weaning growth rate. The results showed heritability values weaning weight, weight of one year and post-weaning growth rate include high category, respectively were 0.62 ± 0.40, 1.05 ± 0.59 and 1.25 ± 0.63. The value of genetic correlation between weaning weight and weight one year post-weaning growth rate was positive and included high category, each is 0.51 and 0.55. This means that selection on weaning weight increase will be followed also by the increasing weight of one year and post-weaning growth rate, selection on weaning weight will accelerate the implementation of selection of the parameters related to meat production, so as to increase the selection response per year.